PKM Pendampingan Laporan Keuangan Berbasis Digital dan Pemasaran Digital pada Kelompok Desa Sirumbia, Kecamatan Simpang Empat, Kabupaten Karo, Sumatera Utara - Rizki Syahputra; Luckyhasnita, Andam; Ridho Lubis, Arif; Ardi Hutagalung, Gabriel (Jurnal Tiyasadarma, 2025)
Desa Sirumbia in Karo Regency has high economic potential, particularly in the promising coffee cultivation business; however, traditional financial recording methods and limited market reach hinder its development. Despite the availability of internet access, coffee sales from this village remain limited and are not widely recognized. The goal of this activity is to maximize the economic potential of Desa Sirumbia by modernizing financial management and utilizing digital technology to enhance operational efficiency and expand market reach and branding of the coffee products. The partners in this initiative are community groups in Desa Sirumbia engaged in coffee production. The implementation method involves observations and surveys to understand the issues, followed by socialization, training, and assistance in managing digital financial records and marketing strategies through digital media. The results show that participants successfully grasped the basics of accounting based on SAK EMKM to prepare financial reports and effectively utilized the Canva application to create promotional designs in the form of flyers. Evaluation of the activities was conducted through written questionnaires completed by the participants. This community service program has successfully improved the partners' skills in digital financial recording and digital marketing. The training provided solutions to the main challenges faced by the partners, namely limitations in financial management and product marketing. Consequently, the partners can now independently create simple digital financial reports and design digital promotions.